The Application of Fair Value Accounting and Its Impact on Financial Sustainability Evaluation Case Study of Asiacell Telecommunications Company - Taher, Ahmed (The Journal of Accounting and Management, 2025)
This research aims to determine the impact of applying fair value accounting on the assessment of the financial sustainability of local companies (Asiacell Telecommunications Company). The research is based on a main hypothesis that the application of fair value has an impact on the assessment of financial sustainability. To achieve the research objectives, the financial statements of the sample company were used. A set of financial ratios were used to determine the impact of applying fair value accounting on the assessment of the financial sustainability of the sample company. The research concluded that fair value accounting has an impact on Asicell’s financial sustainability. The impact is positive: Fair value accounting improves financial solvency, strengthens equity, and enhances the long-term sustainability picture. The impact is neutral. Regarding liquidity, there are no significant changes in short-term sustainability. Regarding profitability, the impact is slightly negative: the reported surplus/profit decreases slightly due to higher depreciation and fair value adjustments.